ANALISIS KADAR TIMBAL (Pb) DAN HEMOGLOBIN (Hb) PADA PETUGAS PENGECATAN MOBIL DI BENGKEL AUTO BLITZ KOTA PEKANBARU DAN POTENSINYA SEBAGAI RANCANGAN LEMBAR KERJA SISWA BIOLOGI DI SMA - Irchamnil Lutfi; Yustina '; Darmadi Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aimed to analyze the levels of lead (Pb) due to exposure to lead contained in paint and influence on the blood lead levels of hemoglobin (Hb) to workers in the car painting workshop Pekanbaru City Auto Blitz in April-May 2016. This was observational research (Cross Sectional Study) to identify factors associated with blood lead levels such as age, length of employment, alcohol consumption and smoking habits. The population in this study amounted to 45 people with a total sample of 12 respondents, obtained by using total sampling that all officers in the car painting workshop Auto Blitz Pekanbaru totaling 12 people. Descriptive data analysis consists of two stages of the test phase lead levels and hemoglobin in the blood in the laboratory and then compared with a threshold value (NAV) which has been established by WHO and stage design student worksheet. Results showed that the variables of age and length of employment affects blood lead levels, whereas the consumption of alcohol and smoking does not affect blood lead levels. Lead levels in the blood affect hemoglobin levels, where the higher the blood levels of Lead in the lower levels of hemoglobin. The results of the research can then be used as the material enrichment Subjects in High School Biology Class X matter air pollution in draft form students' worksheets.Key Words: Lead (Pb), Hemoglobin (Hb), Design Student Worksheet